Occurrence and Functions of Endophytic Fungi in Crop Species - Nicoletti, Rosario (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In the past few decades, awareness of the basic role that endophytic fungi play in shaping the fitness of both wild and crop plants has increased significantly. The number of papers on the subject is so large that it is becoming difficult to have a complete overview of the state-of-the-art with reference to specific crops. In the absence of readily available documents providing circumstantial information on the endophytic assemblage of plants, the isolation of a certain fungal species may appear to be occasional or trivial; hence, many important findings are at risk of going unnoticed. This Special Issue aims to present a collection of papers dealing with the occurrence and functions of endophytic fungi in crop species. It may represent a useful tool for stakeholders in this particular research field, with a view to stimulating a more thorough consideration of the opportunities deriving from their discoveries.